2013
DOI: 10.3408/jafst.18.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Body Fluid Stains Using Real-time RT-PCR: Discrimination Between Salivary, Nasal, and Vaginal Secretions

Abstract: In a criminal investigation, it is important to clarify the origin of the extracted DNA from available biological samples. In recent years, a new approach for the identiˆcation of body ‰uid stains has been demonstrated and involves a comparison of speciˆc mRNA expression levels. Here, we used real-time RT-PCR to examine the expression levels of STATH, HTN3, MUC4, and ESR1 genes from salivary, nasal, and vaginal secretions which are often thought to be di‹cult to discriminate between. STATH was expressed at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…In particular, real-time RT-PCR using the mRNA expression levels of salivary-specific proteins has been reported [37][38][39]. We have also confirmed the usefulness of the STATH and HTN3 genes [40,41] and performed various studies to introduce the method into practice [42][43][44]. In addition, methods focusing on microRNA [45][46][47][48][49][50] and DNA methylation [51][52][53][54][55][56] have been actively explored for saliva identification.…”
Section: Saliva Identificationsupporting
confidence: 64%
See 2 more Smart Citations
“…In particular, real-time RT-PCR using the mRNA expression levels of salivary-specific proteins has been reported [37][38][39]. We have also confirmed the usefulness of the STATH and HTN3 genes [40,41] and performed various studies to introduce the method into practice [42][43][44]. In addition, methods focusing on microRNA [45][46][47][48][49][50] and DNA methylation [51][52][53][54][55][56] have been actively explored for saliva identification.…”
Section: Saliva Identificationsupporting
confidence: 64%
“…As for saliva and semen, many studies have been conducted using real-time RT-PCR [38,90,91]. We have also performed similar studies [35,41] and have revealed the usefulness of multiplex detection specifically targeting ESR1, SERPINB13, KLK13, CYP2B7P1, and MUC4 genes [92,93] for vaginal fluid identification. Methods using microRNA [45,46,48,49] and DNA methylation [52][53][54][55] are also being examined.…”
Section: Vaginal Fluid Identificationmentioning
confidence: 72%
See 1 more Smart Citation
“…The analysis of body fluid-specific mRNA expression levels has recently been reported as a promising tool for the identification of body fluids in biological stains (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In 2005, Juusola and Ballantyne reported multiplex mRNA profiling for the identification of body fluids using agarose gel electrophoresis and capillary electrophoresis format (8).…”
mentioning
confidence: 99%
“…Therefore, by cut-off absorbance value at 0.2 the PRH1/2 ELISA is useful for saliva identification, despite aging and mixing of samples, which could cause digestion and denaturation of proteins, reinforcing its potential value as a method for forensic saliva identification. HTN3 mRNA has previously been shown to be a good marker for saliva identification [5,22]. However, the protein-based method for detecting HTN3 has not been reported because the useful antibody for forensic investigation cannot be available at present.…”
Section: Discussionmentioning
confidence: 96%